Keanekaragaman Genetik Nyamuk Vektor Filariasis Culex quinquefasciatus Say, 1823 (Diptera: Culicidae) di Kota dan Kabupaten Pekalongan Dengan Metode PCR-RAPD - Anindita Riesti Retno Arimurti (Universitas Muhammadiyah Surabaya, 2018)
Mosquito Culex quinquefasciatus is a vector of nematode worms, namely Wuchereria bancrofti which is the cause of filariasis in tropical and subtropical countries. Distributed of Cx. quinquefasciatus is widely in Indonesia with differences the geographical, resulting in the adaptation to the environment and may results in a high variation, both phenotypic (morphology) and genotypic (genetic) variation. This study aims was to determine the genetic diversity of mosquitoes Cx.quinquefasciatus as vector filariasis in Pekalongan City and Regent. Genetic characterization performed by PCR-RAPD using three primers, ie OPA-11, OPA-12, and OPA-15. Data were analyzed by using UPGMA algorithm and Simple Matching Coefficient and presented as dendrogram. The results showed a high genetic diversity with the polymorphisms up to 100%. Keywords: Culex quinquefasciatus, vector, filariasis, PCR-RAPD